Application of Epineural Sheath as a Novel Approach for Fat Volume Maintenance. Issue 6 (December 2017) - Siemionow, Maria; Uygur, Safak; Madajka, Maria
Abstract : Introduction: Various methods have been suggested to improve fat graft survival and decrease graft loss. The exact mechanism of fat graft survival is still unclear, and new strategies are needed to further investigate it. Materials and Methods: The efficacy of epineural sheath in fat volume maintenance was tested in rat model. Five experimental groups were created: group 1, fat graft without any coverage; group 2, epineural sheath tube alone; group 3, epineural sheath tube filled with fat graft; group 4, fat graft mixed with minced epineural sheath without any coverage; and group 5, fat graft covered with the epineural sheath patch. All grafts were implanted into the dorsal subcutaneous region and were followed for up to 12 weeks, when samples were harvested for hematoxylin and eosin and immunostaining for vascular endothelial growth factor expression and perilipin evaluation of fat viability. Results: In groups 1 and 4, over 25% of graft loss was observed at first week, over 50% at third week, and 100% at sixth week postimplantation. The weight of fat graft within the epineural sheath tube and the weight of epineural tube (ET) alone were maintained up to 12 weeks postimplantation. The weight of fat graft within the epineural patch was maintained up to 6 weeks, but 50% of weight loss was observed between 6 and 12 weeks. Structure of the epineural sheath tubes and patches was intact, and no leakage of fat graft was observed. Based on hematoxylin and eosin staining, normal structure and integrity of the fat graft within the ET were preserved up to 12 weeks postimplantation. Characteristic adipocyte morphology was confirmed by perilipin staining, showing viable fat cells in groups 3 and 5 at 12 weeks. Increased vascular endothelial growth factor expression was observed in groups 2, 3, 4, and 5. Conclusions: Both, the ETs and epineural patches maintained 100% and 50% of fat graft weight at 12 weeks postimplantation, respectively. These results were confirmed by histology and immunostaining showing viable adipocytes within the epineural patches (6 weeks) and tubes (12 weeks). These results are encouraging and justify further evaluation of fat volume maintenance in preclinical large animal model in preparation to clinical application.